Political stability and fiscal policy: time series evidence for the Swiss federal level since 1849 - Feld, Lars P.; Schaltegger, Christoph A. (Public choice, 2010)
This paper explores the role of political stability on fiscal policy in a time-series analysis over 158 years at the Swiss federal level. We argue that the fiscal commons problem of public finances is affected by the number of years a finance minister remains in office, because the incentives for an incumbent to maintain a good reputation with sound policy decisions are stronger. A finance minister who succeeds to stay a long time in office enjoys a politically powerful position towards the administration, parliament and interest groups. In contrast, frequent government turnover weakens the position of the finance minister.